On the critical particle size of soil with clogging potential in shield tunneling - Shuying Wang; Zihao Zhou; Pengfei Liu; Zhao Yang; Qiujing Pan; Weizhong Chen (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
Shield tunneling is easily obstructed by clogging in clayey strata with small soil particles. However, soil clogging rarely occurs in strata with coarse-grained soils. Theoretically, a critical particle size of soils should exist, below which there is a high risk of soil clogging in shield tunneling. To determine the critical particle size, a series of laboratory tests was carried out with a large-scale rotary shear apparatus to measure the tangential adhesion strength of soils with different particle sizes and water contents. It was found that the tangential adhesion strength at the soil–steel interface gradually increased linearly with applied normal pressure. When the particle size of the soil specimen was less than 0.15 mm, the interfacial adhesion force first increased and then decreased as the water content gradually increased; otherwise, the soil specimens did not manifest any interfacial adhesion force. The amount of soil mass adhering to the steel disc was positively correlated with the interfacial adhesion force, thus the interfacial adhesion force was adopted to characterize the soil clogging risk in shield tunneling. The critical particle size of soils causing clogging was determined to be 0.15 mm. Finally, the generation mechanism of interfacial adhesion force was explored for soils with different particle sizes to explain the critical particle size of soil with clogging risk in shield tunneling.